Brief screening tests during acute admission in patients with mild stroke are predictive of vascular cognitive impairment 3–6 months after stroke. Issue 6 (11th April 2012) - Dong, YanHong; Venketasubramanian, Narayanaswamy; Chan, Bernard Poon-Lap; Sharma, Vijay Kumar; Slavin, Melissa Jane; Collinson, Simon Lowes; Sachdev, Perminder; Chan, Yiong Huak; Chen, Christopher Li-Hsian
Abstract : Objectives: To determine the prognostic value of brief cognitive screening tests administered in the subacute stroke phase (initial 2 weeks) for the detection of significant cognitive impairment 3–6 months after stroke, the authors compared the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE). Methods: Patients with ischaemic stroke and transient ischaemic attack were assessed with both MoCA and MMSE within 14 days after index stroke, followed by a formal neuropsychological evaluation of seven cognitive domains 3–6 months later. Cognitive outcomes were dichotomised as either no–mild (impairment in ≤2 cognitive domains) or moderate–severe (impairment in ≥3 cognitive domains) vascular cognitive impairment. Area under the receiver operating characteristic (ROC) curve analysis was used to compare discriminatory ability. Results: 300 patients were recruited, of whom 239 received formal neuropsychological assessment 3–6 months after the stroke. 60 (25%) patients had moderate–severe VCI. The overall discriminant validity for detection of moderate–severe cognitive impairment was similar for MoCA (ROC 0.85 (95% CI 0.79 to 0.90) and MMSE (ROC 0.83 (95% CI 0.77 to 0.89)), p=0.96). Both MoCA (21/22) and MMSE (25/26) had similar discriminant indices at their optimal cutoff points; sensitivity 0.88 versus 0.88; specificity 0.64 versus 0.67; 70% versus 72% correctly classified. Moreover, both tests had similar discriminant indices in detecting impaired cognitive domains. Conclusions: Brief screening tests during acute admission in patients with mild stroke are predictive of significant vascular cognitive impairment 3–6 months after stroke.